Ameliorative effects of different doses of selenium against fluoride-triggered apoptosis and oxidative stress-mediated renal injury in rats through the activation of Nrf2/HO-1/NQO1 signaling pathway. (April 2023) - Hu, Yingjun; Yan, Zipeng; He, Yang; Li, Yan; Li, Meng; Li, Yuanyuan; Zhang, DingLi; Zhao, Yangfei; Ommati, Mohammad Mehdi; Wang, Jundong; Huo, Meijun; Wang, Jinming
Abstract: Excess fluoride (F) exposure can cause oxidative stress in the kidney. As an antioxidant, selenium (Se) can potentially protect the kidney from F-induced injury in rats. Hence, the histopathological, renal biochemical, oxidative stress, and apoptotic-related indices upon exposure to 100 mg/L sodium fluoride (NaF) and various doses of sodium selenite (Na2 SeO3 ; 0.5, 1, and 2 mg/L) were assessed. Our results demonstrated that F-mediated renal structural damage and apoptosis elevated the content of serum creatinine (SCr), inhibited the activity of catalase (CAT) in serum, and increased the production of reactive oxygen species (ROS) in kidney and malondialdehyde (MDA) in serum. Interestingly, 1 mg/L dietary supplementation of Se tangibly mitigated these injuries. Furthermore, F could also change the gene and protein expression of the nuclear factor erythroid 2-related factor 2 (Nrf2), heme oxygenase-1 (HO-1), and NAD(P)H quinone oxidoreductase1 (NQO1). Concomitantly, the different concentrations of Se notably alleviated their expression. Taken together, 1–2 mg/L Se ameliorated F-induced renal injury through oxidative stress and apoptosis-related routes. The recorded ameliorative effects might be related to the activation of the Nrf2/HO-1/NQO1 signaling pathway. Graphical abstract: Image 1 Highlights: 100 mg/L NaF exposure altered biochemical indicators related to kidney metabolism and oxidative indices, as well as caused renal injury in rats. Supplementation of 1-2 mg/L Na2SeO3 ameliorated fluoride-triggered apoptosis and oxidative stress-mediated renal injury. Se supplementation mitigated F-induced kidney oxidative stress and apoptosis through the Nrf2/HO-1/NQO1 signaling pathway.